File Search on an FTP Server Using the Fuzzywuzzy Method and the DFS Algorithm - Syuhur, Naufal Saidhus; Jokonowo, Bambang; Wijaya, Agil Dwiki (Journal Collabits, 2024)
The Depth-First Search (DFS) algorithm can be used to search for files on an FTP server. The fuzzywuzzy method can be applied to perform fuzzy string matching for the file names. To implement this, one can establish a connection to the FTP server using a programming language that supports FTP operations, retrieve the file listings using DFS, apply fuzzy matching to the file names, and retrieve the matching files. The fuzzywuzzy method is a string matching library that uses the Levenshtein Distance to calculate the differences between sequences. While there are no specific examples of using DFS with fuzzywuzzy on an FTP server, the general approach can be implemented using ftplib in Python for FTP operations and the fuzzywuzzy library for fuzzy string matching.